Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1167/iovs.09-3538
|View full text |Cite
|
Sign up to set email alerts
|

Test–Retest Reliability of Saccadic Measures in Subjects at Risk for Huntington Disease

Abstract: Good reliability of saccadic latency and percentage of errors in both antisaccade and memory-guided tasks suggests that these measures could serve as biomarkers to evaluate progression in HD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 30 publications
3
22
0
1
Order By: Relevance
“…Study participants were recruited primarily from individuals who had taken part in previous HD research studies at Indiana University [4, 10, 21]. The study was approved by the institutional review board at Indiana University, and all participants gave informed consent prior to their inclusion in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Study participants were recruited primarily from individuals who had taken part in previous HD research studies at Indiana University [4, 10, 21]. The study was approved by the institutional review board at Indiana University, and all participants gave informed consent prior to their inclusion in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Saccades are typically slow and hypometric, and the more 'voluntary' types of saccade, such as anti-saccades and memory guided saccades, are particularly affected [5,6,24,25]. Saccadic reaction times or latency may be affected, though previously we have shown that it is more useful to look not just at mean latencies, but at their distributions, abnormalities of which can provide important quantitative neurological information that can be related to our knowledge of the underlying neural mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Also, increased saccadic latencies (Blekher et al, 2006;Golding et al, 2006;Robert et al, 2009) and errors in saccadic direction have been reported in presymptomatic stages (Blekher et al, 2006). These results suggest that measures of saccadic movements are a possible indicator of disease stage in HD (Blekher et al, 2009). However, whether oculomotor performance parameters can be used to classify individuals according to their disease stage remains to be seen.…”
mentioning
confidence: 66%
“…Nonetheless, the replicability of measures within short time spans is important. The study by Blekher et al (2009) has shown that saccade latency and the percentage of errors have moderate to high replicability in control and premanifest HD groups (see also Klein & Fischer, 2005), whereas gain and velocity only present moderate reliability. Moreover, the replicability of the latter did not reach significance in a simple visually guided (prosaccade) task.…”
Section: Discussionmentioning
confidence: 98%